Indian clinical practice consensus guidelines for the management of recurrent, persistent, or metastatic squamous cell carcinoma of head-and-neck - Update 2023 - Vanita Noronha; K Govind Babu; HS Darling; Pankaj Chaturvedi; Moni Kuriakose; Abhishek Mahajan; Praveen Birur; Ashish Kaushal; Manish Singhal; Munish Gairola; Sumit Goyal; M Vijay Patil; et al. (Cancer Research, Statistics, and Treatment)
Head-and-neck squamous cell carcinoma (HNSCC) remains a significant public health concern, particularly in India, where its incidence is disproportionately high due to risk factors such as tobacco and alcohol use. The updated guidelines for the management of HNSCC reflect a comprehensive review of current evidence and practices tailored to the Indian context. They emphasize a multidisciplinary approach and the integration of novel therapeutic modalities, including immune checkpoint inhibitors and metronomic chemotherapy. Enhanced diagnostic protocols and a focus on supportive care underscore the commitment to improving patient outcomes and quality of life. This update aims to provide healthcare professionals with clear, evidence-based recommendations that address the unique challenges faced by patients with HNSCC in India.